Answer:
-2
Step-by-step explanation:
You make x= -3 then you insert it into the problem which is x= 2(-3)+4
2 times -3 is -6 which then you would get
-6+4 which equals -2
Answer:
C=8k+24
Step-by-step explanation:
Answer:
0'777
+765
Step-by-step explanation:
Hello :
the center of this cercle is : O( 0, 0)
calculate the slope m of the line : OA .. A (3,-4)
m= (yA - yO) / (xA- xO)
m = (-4-0)/(3-0)
m= -4/3
if : k the slope of the tangent : k×m = -1 (the tangent perpendiclar of : OA)
k× (-4/3) = -1
k = 3/4
an equation of this tangent is : y - (-4) = (3/4)(x-3)
Answer:
12
Step-by-step explanation: